Measurement Development and Validation for Construct Validity of the Treatment: The Grief Recovery Method® Instrument (GRM-I). - Nolan, Rachael D.; Hallam, Jeffrey S. (American Journal of Health Education)
Background: Death education is focused on the lifestyle behavioral and emotional aspects of grief. Although several interventions exist that aim to influence grief, many have not been theoretically examined and have lacked valid and reliable instrumentation. Purpose: This study described a construct validity approach used to develop and validate the Grief Recovery Method® Instrument (GRM-I), a measure used to assess implicit theoretical variables of an intervention intended to influence grief and promote grief recovery. Methods: Content analysis of the program handbook, expert panel, and peer review were used to develop items. A pilot study and field and validity tests were used for validation purposes. Internal consistency was assessed using Cronbach's alpha. Results: Confirmatory analysis (n = 279) showed an overall adequate fit of the data to the hypothesized factorial structure (normed fit index = 0.97; relative fit index = 0.83; incremental fit index = 0.97; Tucker-Lewis index = 0.87; comparative fit index = 0.98; parsimony normed fit index = 0.19; parimony comparative fit index = 0.20; and root mean square error of approximation = 0.09). Cronbach's alpha for the full measure was 0.87. Discussion: This study established the GRM-I as a content valid and reliable measure. Translation to Health Education Practice: With future evaluative use of the GRM-I to test the implicit theoretical structure of the death education intervention, research will be able to show how and to what extent intervention components influenced variables of grief and grief recovery.